Uncontrolled Hypertension and Behavioral Risk Factors among Adult Hypertensive Patients at Saint Paul’s Hospital, Millennium Medical College, Addis Ababa, Ethiopia - Yemisirach Sisay; Hana Abera; Tolesa Diriba Biratu; Tesfaye Girma Legesse (Advances in Public Health)
Introduction. Uncontrolled hypertension is a state of systolic blood pressure ≥140 mm Hg and/or diastolic blood pressure ≥90 mm Hg even though the patients are on antihypertension. The WHO states that it is the most prevalent risk factor for death and disability worldwide, particularly in developing nations. The goal of the current study was to investigate behavioral risk factors for uncontrolled hypertension among adult hypertensive patients in Ethiopia. Methods. From October to November 2020, a cross-sectional study design was carried out in the hypertension follow-up clinic at Saint Paul’s Hospital, Millennium Medical College. The choice of 474 study participants was made using a straightforward random sampling method. A semistructured questionnaire was used to obtain data through a chart review as well as an interview. The data were coded before being imported into Epi-data version 7.0 and exported to SPSS version 25 for analysis. To determine the factors associated with uncontrolled hypertension, a multivariate logistic regression model (AOR, 95% CI, and p value 0.05) was used. Result. This study found that 52.1% of hypertensive patients had uncontrolled hypertension. Among hypertensive patients who are alcoholics, smokers, or salt consumers, the odds of having uncontrolled hypertension are AOR = 16.7, 95% CI = (8.13–34.346); AOR = 7.4, 95% CI = (1.211–45.29); and AOR = 13.4, 95% CI = (7.355–25.098), respectively. Uncontrolled hypertension is 3 (AOR and 95% CI) and 1.5 (AOR and 95% CI) times more prevalent in illiterates and obese people, correspondingly. Hypertensive patients from urban areas, those who did not engage in physical activity, and those who were overweight had uncontrolled hypertension odds that were 0.55, 0.43, and 0.25 (AOR and 95% CI) times lower, respectively. Conclusion. Uncontrolled hypertension is very common among adult hypertensive patients at the hospital. Behavioral practices and lifestyles factors have a strong association with uncontrolled hypertension. Health education and awareness are on the effect of poor behavior practices and lifestyles to increase adherence to hypertension-controlling medical advice.